PENGARUH MODEL RME BERBANTUAN MEDIA PEMATH TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA - Sischa Ilma Nafia; Himmatul Ulya; Savitri Wanabuliandari (Jurnal Karya Pendidikan Matematika, 2023)
This research is motivated by the lack of ability to understand mathematical concepts. This research was conducted with the aims of 1) testing the average ability of students' understanding of mathematical concepts using the RME model assisted by Pemath media to be better than the average using the direct model; 2) to examine the difference in the average ability of students' understanding of mathematical concepts before and after being taught the RME model assisted by Pemath's media; 3) testing the increase in the ability to understand students' mathematical concepts after being taught with the RME model assisted by Pemath media. This research is a quantitative experimental research. Sampling using random sampling technique. The statistical analysis of the research data is the normality test, homogeneity test, and hypothesis test. The results showed that the average ability to understand mathematical concepts of students using the RME model assisted by Pemath media was better than the average using the direct model, 2) the average ability of students to understand mathematical concepts was better after using the RME model assisted by Pemath media, 3) the ability to understand students' mathematical concepts increases after being taught with the RME model assisted by Pemath media.